Effectiveness of EDUWAP in Increasing Knowledge about Stunting - Cahaya Indah Lestari; Rizkia Amilia; Catur Esty Pamungkas; Evi Diliana Rospia; Dwi Kartika Cahyaningtyas (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2023)
The prevalence of stunting in Indonesia is 24.4 percent, East Lombok Regency is around 43.52 percent. Teenagers are a potential group as agents of behavior change. For this reason, teenagers need to be given education to increase their knowledge and build awareness of the impact of stunting in the future. This research aims to determine the effectiveness of EDUWAP (Education via WhatsApp) in increasing teenagers' knowledge about stunting. The type of research used was Quasy Experimental pretest and posttest with a control group. The population in this study were all young women at SMA Negeri 1 Aikmel in March 2023, with a sample of 30 people who were divided into 2 groups with 15 members each and used a purposive sampling technique. Data collection was carried out using a questionnaire to determine the level of knowledge of young women about stunting before and after the intervention. The post-test statistical results of the experimental group and control group using the Mann-Whitney technique showed Asymp. signature. (2-tailed) 0.012 less than 0.050 with a mean rank for the experimental group of 19.00 and a mean rank for the control group of 12.00. So it can be concluded that there is a significant difference in the post-test results of the experimental group and the control group which influences the increase in knowledge in the experimental group before and after being given treatment towards increasing teenagers' knowledge about stunting.